Counselor-Parent Communication Dynamics in Enhancing Students’ Psychological Well-Being: A Qualitative Literature Review - Risma Nursyani; Nadia Aulia Nadhirah; Nandang Budiman; Syarif Bin Muhammad Romli Samae (JIGC (Journal of Islamic Guidance and Counseling), 2025)
Effective collaboration between school counselors and parents is increasingly recognized as a vital determinant of students’ psychological well-being. While extensive research has explored communication between teachers and students, fewer studies have specifically examined the counselor–parent relationship and its implications for student outcomes, particularly in the Indonesian context. This study aims to analyze the dynamics of counselor–parent communication and its role in enhancing students’ psychological well-being through a qualitative literature review. The review synthesizes findings from national and international research published between 2015 and 2023, focusing on counselor–parent partnerships, communication strategies, and student well-being. Data were obtained from journal articles, books, and conference proceedings, and analyzed thematically to identify patterns, challenges, and best practices in counselor–parent collaboration. Findings highlight that effective communication is characterized by respect, empathy, clarity, and humility, enabling counselors and parents to build mutual trust and cooperative relationships. Moreover, communication serves not only to exchange information but also to align expectations, reduce conflict, and strengthen support systems that directly influence students’ emotional resilience and school engagement. These results resonate with international literature emphasizing parental involvement as a predictor of student adjustment and well-being. This study contributes to the literature by situating counselor–parent communication within the broader discourse on educational counseling and psychological well-being. Practically, it provides insights for schools and policymakers to design communication frameworks that foster collaborative partnerships between counselors and families.